Distinct peripheral B-cell immunophenotypes define clinical heterogeneity in childhood-onset systemic lupus erythematosus - Li-Yun Xu; Hui Chen; Yong-Zhen Li; Lan Luo; Ming Yang; Xiao-Chuan Wu (World Journal of Pediatrics, 2026)
Abstract Background B-cell dysregulation is central to the pathogenesis of childhood-onset systemic lupus erythematosus (cSLE), yet the B-cell immunophenotypes across disease states remain incompletely defined. This study aimed to investigate the mechanistic basis and clinical relevance of B-cell–mediated immune dysregulation in cSLE. Methods Peripheral blood samples from 64 cSLE patients and 40 age- and sex-matched healthy controls (HCs) were analyzed using flow cytometry. The subsets were compared across disease states, including lupus low disease activity state (LLDAS), active disease, and clinical flare. Diagnostic performance was evaluated using logistic regression and receiver operating characteristic analyses. Results Compared with HCs, patients with cSLE exhibited reduced unswitched memory B cells and expanded pathogenic subsets, including double-negative (DN) B cells, age-associated B cells (ABCs), short-lived plasma cells (SLPCs), and long-lived plasma cells (LLPCs) (all P < 0.05). LLPCs showed the strongest disease association [area under the curve (AUC) = 0.855] and a combined model further improved discrimination (AUC = 0.936). Active disease was characterized by expanded DN B cells, ABCs, SLPCs, and LLPCs (all P < 0.05). Clinical flare involved selective enrichment of ABCs, DN B cells, and plasma cells without further increase in total B cells. Of note, LLPCs remained elevated in LLDAS compared with HCs ( P < 0.01). ABCs were negatively correlated with complement C3 levels ( r = − 0.26, P = 0.04). Conclusions cSLE is characterized by distinct peripheral B-cell immunophenotypes across different clinical states, marked by expansion of ABCs and plasma-cell populations. Persistent LLPC enrichment during clinical quiescence suggests incomplete immunological restoration and may contribute to disease heterogeneity and relapse susceptibility.